Cistercian Financial Organisation, 1335–1392 - King, H. Peter (The journal of ecclesiastical history, 1973)
Fourteenth-century records give a depressing picture of the finances of the Cistercian Order. In 1338, for instance, the Chapter General stated that the Order was heavily in debt at the papal curia and in the fairs of Champagne, and that its income was not sufficient to meet all its obligations. Its immunity from papal and royal taxation had been largely eroded in the thirteenth century. During the Avignon period the popes levied frequent property taxes from the Church in France, and by an arrangement with the French monarchy, the lion's share of the profits went to the king. In this way Philip VI obtained money from the Church during the Hundred Years’ War. The premier abbeys of the Cistercian Order, and its other houses within the kingdom, were not exempt from these exactions, and no doubt shared the distress of the French clergy. In 1362 Urban V refused to levy another property tax from the Church in France, on the grounds that it had paid more than enough.